A detailed overview of quercetin: implications for cell death and liver fibrosis mechanisms - Fei Xiong; Yichen Zhang; Ting Li; Yiping Tang; Si-Yuan Song; Qiao Zhou; Qiao Zhou; Yi Wang (Frontiers Media S.A., 2024)
BackgroundQuercetin, a widespread polyphenolic flavonoid, is known for its extensive health benefits and is commonly found in the plant kingdom. The natural occurrence and extraction methods of quercetin are crucial due to its bioactive potential.PurposeThis review aims to comprehensively cover the natural sources of quercetin, its extraction methods, bioavailability, pharmacokinetics, and its role in various cell death pathways and liver fibrosis.MethodsA comprehensive literature search was performed across several electronic databases, including PubMed, Embase, CNKI, Wanfang database, and ClinicalTrials.gov, up to 10 February 2024. The search terms employed were "quercetin", "natural sources of quercetin", "quercetin extraction methods", "bioavailability of quercetin", "pharmacokinetics of quercetin", "cell death pathways", "apoptosis", "autophagy", "pyroptosis", "necroptosis", "ferroptosis", "cuproptosis", "liver fibrosis", and "hepatic stellate cells". These keywords were interconnected using AND/OR as necessary. The search focused on studies that detailed the bioavailability and pharmacokinetics of quercetin, its role in different cell death pathways, and its effects on liver fibrosis.ResultsThis review details quercetin's involvement in various cell death pathways, including apoptosis, autophagy, pyroptosis, necroptosis, ferroptosis, and cuproptosis, with particular attention to its regulatory influence on apoptosis and autophagy. It dissects the mechanisms through which quercetin affects these pathways across different cell types and dosages. Moreover, the paper delves into quercetin's effects on liver fibrosis, its interactions with hepatic stellate cells, and its modulation of pertinent signaling cascades. Additionally, it articulates from a physical organic chemistry standpoint the uniqueness of quercetin's structure and its potential for specific actions in the liver.ConclusionThe paper provides a detailed analysis of quercetin, suggesting its significant role in modulating cell death mechanisms and mitigating liver fibrosis, underscoring its therapeutic potential.